2017
DOI: 10.1002/hbm.23929
|View full text |Cite
|
Sign up to set email alerts
|

Networks of myelin covariance

Abstract: Networks of anatomical covariance have been widely used to study connectivity patterns in both normal and pathological brains based on the concurrent changes of morphometric measures (i.e., cortical thickness) between brain structures across subjects (Evans, 2013). However, the existence of networks of microstructural changes within brain tissue has been largely unexplored so far. In this article, we studied in vivo the concurrent myelination processes among brain anatomical structures that gathered together e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 129 publications
(214 reference statements)
3
35
0
Order By: Relevance
“…Our data support the use of T1-w/T2-w ratio to measure myelin covariance -our structural covariance networks demonstrated organization as well as high and symmetric intra-hemispheric connectivity in both children and adults, consistent with our previous study using MT (15). Myelin covariance is highest between the bilateral subcortical and limbic structures, both within and between hemispheres, and amongst within-hemispheric connections in the occipital and parietal lobes (particularly in the adults), as seen by Melie-Garcia et al (24).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data support the use of T1-w/T2-w ratio to measure myelin covariance -our structural covariance networks demonstrated organization as well as high and symmetric intra-hemispheric connectivity in both children and adults, consistent with our previous study using MT (15). Myelin covariance is highest between the bilateral subcortical and limbic structures, both within and between hemispheres, and amongst within-hemispheric connections in the occipital and parietal lobes (particularly in the adults), as seen by Melie-Garcia et al (24).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies examining typical development from childhood to young adulthood, the age-related changes of both structural covariance (24)(25)(26)(27) and MEG functional connectivity (28)(29)(30) follow predominantly nonlinear, quadratic trajectories. The differences in functional connectivity with age was marked by increases in functional connectivity with age in the alpha and beta bands and decreases in the gamma bands, consistent with developmental changes reported in both phase-based (31) and amplitude (30, 32) connectivity measures.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rather, it has been observed that distinct networks tend to covary with respect to myelin changes with age ( Evans, 2013 ). Interestingly, these network correlations in myelination changes were shown to potentially increase the resilience of covarying networks to damage, using simulations in which network hubs were deleted ( Melie-Garcia et al, 2018 ). Thus, the specific changes in connectivity that occur in the aging brain may confer improved resistance to increasingly probable network damage as individuals age.…”
Section: Does Myelin Plasticity Have a Critical Period?mentioning
confidence: 99%
“…) and myelin content(35)). Crucially, quantitative MRI maps are impervious to inter-site variability ( (49)).…”
mentioning
confidence: 99%